Identificação e determinação do anetol em plasma de rato por cromatografia líquida de alta eficiência de fase reversa - Fagundes, Vinicius Henrique Veraldo (2011)
Essential oils are composed of secondary metabolites of plants and thay are important in the metabolism of these presenting diverse biological activities. The anethole, or transanethole (trans-1-methoxy-4-(prop-1-enil) benzene), is a major constituent of essential oil from star anise (Illicium verum Hook). An unusual topic investigated in the literature, is the study of bioavailability of essential oils. It was not described in the literature, a method using liquid chromatography (HPLC), with a purpose to make a bioavailability study using plasma of human or animals. The objective of this study was the identification and quantification of anethole present in the essential oil of star anise, and proposes a method of quantification of anethole by liquid chromatography of reverse phase, using the rat plasma as matrix, and for Identification was used NMR, GC-MS and HPLC. The validation method of analysis of anethole in plasma, were performed using as mobile phase methanol: water (85:15). The compound was extracted from plasma by precipitation with methanol at low temperature, even the compound being apolar. The validation results were satisfactory with R2 above 0.99 and the precision present a standard deviation less than 6%.